RESEARCH ON BENDING STRESS OF COMPOSITE MATERIALS COMPONENT WITH EMBEDDED CABLE - ZHUANG GongWei; WU ZhaoHua; XU HuiYu; LIU YaTao; CHEN XiaoYong (Jixie qiangdu)
The composite materials component with embedded cable three point bending stress finite element analysis model was established,and the influence of cable embedding position,resin enrichment zone length and cable diameter on the bending stress of the component was analyzed under the three point bending load to the same bending load. The results show that the closer the cable is embedded in the composite surface,the greater the bending stress of the component. With the length of the resin enrichment zone increase,the bending stress of the component increases. With the diameter of the cable increase,the bending stress of the component increases. With 90% confidence,the cable embedding position has a significant influence on the maximum bending stress,the resin length and cable diameter have no significant effect on the maximum bending stress of the component. The cable embedding position,cable diameter,resin length affect the maximum bending stress of the component in a descending order. The research conclusion provides a theoretical basis for the cable embedded composite technology.